Penerapan Algoritma Brute Force Pada Sistem Informasi Perpustakaan SD Negeri 15 Muara Dua Berbasis Web - Sujacka Retno, Nurhayati, T Irfan Fajri (Jurnal Elektro dan Informatika, 2022)
Libraries are one of the facilities owned by educational institutions in their service efforts in the field of education. The role of the library is very important in providing scientific books for students and teachers in an effort to provide maximum service. Therefore, the library always increases the number of books provided. With the large number of books, the librarian will certainly have difficulty in finding the book data contained in the library. Therefore, this study aims to create a library system that is expected to help facilitate the management process related to library activities such as borrowing books, returning books, inputting book data and so on. This system is built using the PHP programming language by adding a Brute Force algorithm to help facilitate the search for large number of book data.